2022
DOI: 10.1186/s12879-022-07945-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of Covid-19 illness and predictors of in-hospital mortality in Saudi Arabia

Abstract: Background Patients’ race and ethnicity may play a role in mortality from Covid-19. Studies in China, the US, and Europe have been conducted on the predictors of Covid-19 mortality, yet in the EMR countries, such studies are scarce. Therefore, we aimed to describe the hospitalization rate, ICU-admission, and in-hospital mortality of Covid-19 and predictors of in-hospital mortality in Saudi Arabia. Methods E-medical records were examined for all Cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In another study in Saudi Arabia, out of over l 35,284 COVID-19 patients, 81.8% were adults, and 21.7% were hospitalized. Compared to non-hospitalized patients, hospitalized patients had more women (52.1% vs. 47.3%, and an elevated incidence of diabetes mellitus, arterial hypertension, coronary artery disease, cancer, COPD, and asthma (Abolfotouh et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…In another study in Saudi Arabia, out of over l 35,284 COVID-19 patients, 81.8% were adults, and 21.7% were hospitalized. Compared to non-hospitalized patients, hospitalized patients had more women (52.1% vs. 47.3%, and an elevated incidence of diabetes mellitus, arterial hypertension, coronary artery disease, cancer, COPD, and asthma (Abolfotouh et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, the inclusion of CT tests and laboratory values in our study was contingent upon whether the doctors ordered these tests. Therefore, we were unable to incorporate CT tests and laboratory values in our study, even though they have been found to be associated with disease severity in the hospitalized population 48,49 . However, based on our current knowledge, these factors have not been included in previous studies conducted specifically on outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we were unable to incorporate CT tests and laboratory values in our study, even though they have been found to be associated with disease severity in the hospitalized population. 48,49 However, based on our current knowledge, these factors have not been included in previous studies conducted specifically on outpatients. This could also be related to the incomplete availability of CT tests and laboratory values data for outpatient patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, they only limit themselves to comparing textual information. Abolfotouh et al (2022) used records of patient characteristics such as comorbidities, laboratory findings, hospitalization, admission to Intensive Care Units (ICU), and in-hospital and overall mortality, with the aim of describing hospitalization rates, ICU admission, and identifying predictors of in-hospital mortality for COVID-19, that is, they identify causes of in-hospital mortality but do not make predictions of either COVID-19 detection or severe cases. For their part, the work proposed by Perez et al (2021) performed a multivariate logistic regression analysis to determine the effects of age, sex, previous medical condition, and COVID-19 symptoms to determine the probability of positive cases and hospitalizations during the first wave of the pandemic, March-April 2020, but do not make predictions of severe cases, intubated cases, and cases requiring ICU admission.…”
Section: Literature Reviewmentioning
confidence: 99%